Exogenous Cushing’s Syndrome with Steroid-Induced Adrenal Insufficiency Complicated by Sepsis and a Non-healing Diabetic Foot Ulcer: A Case Report - Prajapat, Hardik; Siddiqui, Meharunisha; Tak, Daizy; Parihar, Narendra Bheemraj; Joseph, Jishi Joshi; Rathore, Mahendra Singh (Journal of Pharmacy Practice and Community Medicine, 2026)
This case involves a 52-year-old man with subsequent development of Exogenous Cushing’s syndrome and steroid induced adrenal insufficiency after 1 year of unmonitored betamethasone therapy for Arthritis. The patient reported a 4 months old ulcer of the left foot, accompanied by newly detected type 2 diabetes mellitus. Investigations showed exogenous hypercortisolism complicated by sepsis, hypoalbuminemia, raised transaminases and leucocytosis. Radiographic assessment identified absence of the left kidney. The patient was managed in the ICU with a multidisciplinary approach, including intravenous antibiotics, stress dose intravenous hydrocortisone, strict glycemic control, and later transition to a tapering oral corticosteroid regimen. This case illustrates consequences of chronic exogenous corticosteroid exposure and emphasizes the importance of judicious steroid use, vigilant monitoring for Hypothalamic-Pituitary Axis (HPA) axis suppression, and prompt management of secondary infections.
Keywords: Betamethasone; Exogenous Cushing’s syndrome; Hypoalbuminemia; Steroid induced; adrenal insufficiency; Type 2 diabetes mellitus